A Study on University Students’ Self-Regulated Motivation to Improve EFL Speaking Skills Across Academic Levels - Warni, Silih; Apoko, Tri Wintolo; Martriwati, Martriwati; Nongkhai, Angsu-orn Na (Journal of Languages and Language Teaching, 2024)
opportunities to speak English in class. Self-regulated learning enables some self-motivated students to find opportunities outside the classroom to have face to face and virtual interaction to enhance their English speaking. This study is intended to examine the level of self-regulated motivation of university students to improve their Speaking of English as a foreign language (SRMIS-EFL). Moreover, this study investigates if students' SRMIS-EFL differ accross academic levels. 156 EFL students from an English Department in a private university in Jakarta took part in this study. Self-reported SRMIS-EFL questionnaire was used as the data collecting method. Descriptive and inferential statistical analysis was then conducted. The findings showed that the overall SRMIS-ELF level of students was high. Moreover, students used various self-regulatory motivation strategies to enhance their EFL speaking skills. As for the aspect of academic level, the results of this study shows that SRMIS-EFL of senior students are lower than SRMIS-EFL of junior students , and there is a statistically significant difference of students’ SRMIS-EFL across academic levels. The findings of this study suggest the need for motivational regulation training into EFL programs to increase students’ awareness of motivational self-regulation strategies to enhance their self-regulated motivation.